Digital humanities, libraries, and collaborative research: New technologies for digital textual studies. Issue 2 (3rd April 2019) - Gibson, Twyla
Abstract: How can librarians at college and undergraduate libraries contribute to digital humanities research? This study describes The Greek Key, a working prototype Virtual Research Environment (VRE) for the analysis of texts and manuscripts. This paper explains how the VRE functions through a case study of passages in Plato and the Book of Genesis. The Greek Key VRE is a collaborative, scalable, multidisciplinary project that has the potential to engage librarians in participatory strategies such as crowdsourcing. The VRE will make it possible to pursue perennial questions in innovative ways and to use new technologies to respond to questions that do not lend themselves to more traditional methods.